(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the knowledge and practices regarding preventive dental care among different universities undergraduate students in Karachi, Pakistan. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Dental Biomaterials Department, Jinnah Medical and Dental College, Karachi from September 2017 to December 2017. Materials and Methods: This survey was conducted using a self-administered questionnaire, that assessed oral health and hygiene knowledge and practices of 400 students from various professions (i.e. ACCA, BA, BCOM, BBA, B.S.) Data was analyzed using descriptive statistics and chi-square tests using SPSS VERSION 21. Significance level was set at p<0.05 Results: The survey revealed that 48.8% students used tooth brush with toothpaste and considered as an oral hygiene aid. About 36.5% cleaned their teeth once every morning.57.3% were aware of the role of fluoride in caries prevention.44.3% frequently changed their toothbrush i.e. every 3 months.While 63.0% were aware of the dental problems, occur when oral hygiene is not maintained properly. Conclusion: It can be concluded that most of the students used toothbrush along with toothpaste only, and were not aware of interdental cleaning aids. Interdental cleaning were much below than our expected levels and we must create awareness through programs in educational institutions to reduce the dental disease burden.